Debt holder monitoring and implicit guarantees: Did the BRRD improve market discipline? - Cutura, Jannic Alexander (Journal of Financial Stability, 2021)
This paper argues that the European Union’s Banking Recovery and Resolution Directive (BRRD) has improved market discipline in the European bank market for unsecured debt. The different impact of the BRRD on bank bonds provides a quasi-natural experiment that allows us to study the effects of the BRRD within banks using a difference-in-difference approach. Identification is based on the fact that (otherwise identical) bonds of a given bank maturing before 2016 are explicitly protected from BRRD bail-in. The empirical results are consistent with the hypothesis that debt holders actively monitor banks and that the BRRD diminished bailout expectations after its enactment. Bank bonds subject to BRRD bail-in carry a 13-basis points bail-in premium in terms of the yield spread, driven by low capitalization. Banks that respond to market pressure by de-risking their portfolios are able to secure cheaper funding for instruments that are subject to bail-in.